Inverse majority vertex covering number of a graph - Jayasimman, Paulraj; T, Dhivya; J, Joseline Manora (International Journal of Engineering and Technology, 2018)
A set of vertices , which covers atleast half of the edges is a Majority vertex cover of . The majority vertex covering number Â of is the minimum number in a Majority vertex cover. In this paper, new parameter has been introduced Inverse majority vertex covering number of a graph with respect to Majority vertex covering set. Also majority vertex covering number obtained for classic graphs and Cartesian product graph.